PRAKTIK KOMUNIKASI ANTARPRIBADI GURU BIMBINGAN KONSELING DALAM MENGATASI MASALAH SISWA ANAK USIA DINI - Hadi Ismanto; Maftuh Masyhuri (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This research aims to determine patterns of interpersonal communication between teachers and students with problems, factors that hinder interpersonal communication with students with problems, and the results of interpersonal communication with students with problems. This research methodology is qualitative. The principal, deputy principal for student affairs, supervising teachers, and parents of students at PAUD Aisyiyah Kranji were informants in this research, and communication between parents and teachers in fostering problematic students was the research topic. Based on the research results, interpersonal communication between guidance and counseling teachers and problematic students at PAUD Aisyiyah Kranji was carried out through direct face-to-face meetings and using WhatsApp media, and was proven to be effective in its implementation. Factors that become obstacles to interpersonal communication with guidance and counseling teachers in dealing with problematic students at PAUD Aisyiyah Kranji are students' lack of openness and lack of communication with their school environment. Interpersonal communication between guidance and counseling teachers and students is carried out through direct communication.